The Psychology of Social Networking Vol.1 2015
DOI: 10.1515/9783110473780-010
|View full text |Cite
|
Sign up to set email alerts
|

8. Making and Keeping the Connection: Improving Consumer Attitudes and Engagement in E-Mental Health Interventions

Abstract: E-mental health services are internet-based treatment options

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Although effective, uptake of e-mental health services remains low [ 10 , 11 ]. For example, in a systematic review of computerized cognitive behavioral therapy (cCBT), Waller and Gilbody [ 12 ] reported that only 38% of those recruited into cCBT intervention trials began treatment (median rate), and individuals in cCBT treatments were almost twice as likely to drop out of the intervention as those in active control conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although effective, uptake of e-mental health services remains low [ 10 , 11 ]. For example, in a systematic review of computerized cognitive behavioral therapy (cCBT), Waller and Gilbody [ 12 ] reported that only 38% of those recruited into cCBT intervention trials began treatment (median rate), and individuals in cCBT treatments were almost twice as likely to drop out of the intervention as those in active control conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such initiatives have resulted in the emergence of a number of successful nationwide online services, including ReachOut.com, e-couch, and BluePages, among others (Christensen et al, 2014). Despite this success and the online services providing larger scale and cheaper access to people struggling with mental health issues, a perception continues that face-to-face mental health services provide more effective and better quality support to people (Casey & Clough, 2016;March et al, 2018). The in-person model is regarded as preferable because it is perceived as more trustworthy and allows for a greater level of engagement (March et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This constantly expanding branch of therapy-also referred to as online counseling, Web counseling, Internet psychotherapy, and other terms in different contexts (Barak, Klein, & Proudfoot, 2009;Kyrios & Thomas, 2014;Patrick, 2007)-in contrast to face-to-face therapy, utilizes technology as an integral component in the therapeutic process. This area operates with diverse modalities (Barak, Hen, Boniel-Nissim, & Shapira, 2008;Casey & Clough 2016;Lal & Adair, 2014;Short & Thomas, 2015) and entails therapy enacted through both real-time communication via chat rooms and/or video conferencing (synchronous communication) and time-delayed communication, such as through e-mail or message interfaces (asynchronous communication). Further, online therapy has led to models referred to as "therapist-less therapy" (Short & Thomas, 2015, p. 36), which can include custom-designed apps and websites used to guide clients (or users) through a series of resources and activities, some of which track and respond to progress.…”
Section: Introductionmentioning
confidence: 99%
“…Such initiatives have resulted in the emergence of a number of successful nationwide online services, including ReachOut.com, e-couch, and BluePages, among others (Christensen et al, 2014). Despite this success and the online services providing larger scale and cheaper access to people struggling with mental health issues, a perception continues that face-to-face mental health services provide more effective and better quality support to people (Casey & Clough, 2016;March et al, 2018). The in-person model is regarded as preferable because it is perceived as more trustworthy and allows for a greater level of engagement .…”
Section: Introductionmentioning
confidence: 99%
“…This constantly expanding branch of therapy-also referred to as online counseling, Web counseling, Internet psychotherapy, and other terms in different contexts (Barak, Klein, & Proudfoot, 2009;Kyrios & Thomas, 2014;Patrick, 2007)-in contrast to face-to-face therapy, utilizes technology as an integral component in the therapeutic process. This area operates with diverse modalities (Barak, Hen, Boniel-Nissim, & Shapira, 2008;Casey & Clough 2016;Lal & Adair, 2014;Short & Thomas, 2015) and entails therapy enacted through both real-time communication via chat rooms and/or video conferencing (synchronous communication) and time-delayed communication, such as through e-mail or message interfaces (asynchronous communication). Further, online therapy has led to models referred to as "therapist-less therapy" (Short & Thomas, 2015, p. 36), which can include custom-designed apps and websites used to guide clients (or users) through a series of resources and activities, some of which track and respond to progress.…”
Section: Introductionmentioning
confidence: 99%